2015
DOI: 10.1016/j.jval.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians’ Preferences for Infant Meningococcal Vaccination

Abstract: Physicians' responses indicate a strong preference for infant meningococcal vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 40 publications
(44 reference statements)
2
34
1
Order By: Relevance
“…Our study also found that price was an important attribute driving preferences which is in line with previous research [9, 11, 31, 50, 51]. Recommended but non-publicly funded vaccines were more likely to be refused by parents due to the price [50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also found that price was an important attribute driving preferences which is in line with previous research [9, 11, 31, 50, 51]. Recommended but non-publicly funded vaccines were more likely to be refused by parents due to the price [50].…”
Section: Discussionsupporting
confidence: 91%
“…A positive (negative) and significant coefficient indicates a positive (negative) preference for a specific attribute level. The coefficient estimates (or preference weights) can also be used to compare relative importance between different levels of the same attribute or between levels of completely different attributes [11]. …”
Section: Methodsmentioning
confidence: 99%
“…There were no incentives offered to those who participated in the survey. A sample size of 361 HCWs was calculated by using single population proportion formula with the assumption that 17% of HCWs [ 17 , 20 , 21 , 22 ] would recommend meningococcal vaccinations, a confidence level of 95%, a margin of error at 5%, and a response rate of 60%. The questionnaire, developed by the research team, and based on previously validated questionnaires [ 19 , 23 ], was pilot tested prior to the beginning of the survey in order to ensure that the questions were understood as intended and to omit or reformulate the questions that were misinterpreted.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, most studies evaluating knowledge, attitudes and behaviors about meningococcal disease and related vaccinations have been conducted in the general population [ 17 , 18 , 19 ], or general practitioners (GPs) and paediatricians [ 17 , 20 , 21 ], whereas, to the best of our knowledge, there are no investigations that have been focused on HCWs who provide care to these patients for their underlying medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for this result is inattention to the absolute values of continuous attributes [54]. Some discrete-choice experiment applications in health have found evidence for such inattention [55], while others have not [56]. Good survey design practices can mitigate the problem of inattentive respondents [57].…”
Section: Number Of Attributes and Levelsmentioning
confidence: 99%